Population-based input function (PBIF) applied to dynamic whole-body 68Ga-DOTATOC-PET/CT acquisition - Thuillier, Philippe; Bourhis, David; Pavoine, Mathieu; Metges, Jean-Philippe; Le Pennec, Romain; Schick, Ulrike; Blanc-Béguin, Frédérique; Hennebicq, Simon; Salaun, Pierre-Yves; Kerlan, Véronique; Karakatsanis, Nicolas A.; Abgral, Ronan (Frontiers in Nuclear Medicine, 2022)
Rational To validate a population-based input function (PBIF) model that alleviates the need for scanning since injection time in dynamic whole-body (WBdyn) PET. Methods Thirty-seven patients with suspected/known well-differentiated neuroendocrine tumors were included (GAPETNET trial NTC03576040). All WBdyn 68Ga-DOTATOC-PET/CT acquisitions were performed on a digital PET system (one heart-centered 6 min-step followed by nine WB-passes). The PBIF model was built from 20 image-derived input functions (IDIFs) obtained from a respective number of patients’ WBdyn exams using an automated left-ventricle segmentation tool. All IDIF peaks were aligned to the median time-to-peak, normalized to patient weight and administrated activity, and then fitted to an exponential model function. PBIF was then applied to 17 independent patient studies by scaling it to match the respective IDIF section at 20–55 min post-injection time windows corresponding to WB-passes 3–7. The ratio of area under the curves (AUCs) of IDIFs and PBIF3–7 were compared using a Bland–Altman analysis (mean bias ± SD). The Patlak-estimated mean Ki for physiological uptake (Ki-liver and Ki-spleen) and tumor lesions (Ki-tumor) using either IDIF or PBIF were also compared. Results The mean AUC ratio (PBIF/IDIF) was 0.98 ± 0.06. The mean Ki bias between PBIF3–7 and IDIF was −2.6 ± 6.2% (confidence interval, CI: −5.8; 0.6). For Ki-spleen and Ki-tumor, low relative bias with low SD were found [4.65 ± 7.59% (CI: 0.26; 9.03) and 3.70 ± 8.29% (CI: −1.09; 8.49) respectively]. For Ki-liver analysis, relative bias and SD were slightly higher [7.43 ± 13.13% (CI: −0.15; 15.01)]. Conclusion Our study showed that the PBIF approach allows for reduction in WBdyn DOTATOC-PET/CT acquisition times with a minimum gain of 20 min.